Міста і містечка Чернігівської губернії на початку ХІХ ст. у дорожніх нарисах Івана Долгорукова - Лемешко, Я.C.; Потапенко, М.В. (Сіверщина в історії України, 2021)
У статті здійснюється спроба реконструкції образу міст та містечок Чернігівської губернії, які у 1810 та 1817 роках відвідав князь Іван Долгоруков під час подорожі до Одеси й Києва. Встановлюються ключові складові цього образу. Обґрунтовується теза про високий інформаційний потенціал дорожніх нарисів указаного автора. Робиться висновок про те, що песимістичний образ міст та містечок Чернігівської губернії прописувався свідомо в контексті обґрунтування культурної і політичної опозиції України до Росії. The article reconstructs the image of towns and townships of Chernihiv province, which were visited by Prince Ivan Dolhorukov in 1810 and 1817 during a trip to Odessa and Kyiv. The article basis on a comprehensive analysis of two of his travel notes, which were published by Osip Bodyansky in 1869-1870. During the trip he visited about 10 towns and townships, including Chernihiv, Nizhyn, Hlukhiv, Borzna, Kozelets, Krolevets. The structure of their description is unified. He paid special attention to the description of the location, the town’s infrastructure, the living conditions of travelers, the economic system. Travelogs of Prince Ivan Dolhorukov have a high informative potential. They formed a holistic pessimistic image of towns and townships of Chernihiv province. This was done to bring the cultural and political differences of the newly annexed Ukrainian lands to the Russian Empire.